The Effect of the Recitation Method in Writing Anecdotal Texts for Class X Students of SMA Negeri 1 West Angkola in the 2022-2023 Academic Year - Elnila Caniago; Rini Kesuma SIREGAR (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
This research is based on social studies study result of students is still low, it is necessary to update improving the social studies study results of students and improve the creativity of teachers in managing the learning process. The purpose of this research was to identify (1) how the use of strategy recitation in the teaching of the material Teks Anecdotal class X RPL in SMK Negeri 1 West Angkola year 2022-2023. (2) whether the use of the Strategy recitation could improve learning study Teks Anecdotal the student year 2022-2023. This research was aeksprimen. The subjects of this research were all students 33 fifth-grade students of SMA Negeri 1 West Angkola year 2022-2023. Based on the research result, it may be concluded that: (1) step implementation of learning recitation learning are: the first step is to show the purpose and motivate the students, the second step is to present the information, the third step is to organize students to form a home teams and provide the serial number corresponding to the number of members of the group, the fourth step is helping working groups in the study group of experts discuss to discuss the existing problems, the fifth step is expert teams back to the home teams and each of the team reports the results of the discussion then present the results of the discussion (2) It could be seen from the results of research reached the learning standard of strategi recitacy